Reason & romance a contemporary retelling of Sense and sensibility - Smith, Debra White; Austen, Jane 1775-1817. (Minneapolis, Minnesota Bethany House, a division of Baker Publishing Group, 2018)
Sisters Elaina and Anna Woods face important decisions about love when Anna begins an impulsive romance with Willis Kenney and sensible Elaina finally gives in to her feelings for Ted Farris.
Keywords: Sisters -- Fiction; Mothers and daughters -- Fiction; Man-woman relationships -- Fiction; Inheritance and succession -- Fiction; Christian fiction; Romance fiction